Development of PLA/Mg composite for orthopedic implant: Tunable degradation and enhanced mineralization. (28th July 2017) - Zhao, Changli; Wu, Hongliu; Ni, Jiahua; Zhang, Shaoxiang; Zhang, Xiaonong
Abstract: Polylactic acid (PLA) orthopedic devices suffer from low degradation rate and inadequate osteoconductivity, and often lose efficacy in the late stage of implantation because of inflammatory response of acid products and inability integration to bone. In this work, 2 wt% and 5 wt% magnesium particles reinforced PLA were fabricated using solvent casting and investigated in terms of in vitro degradation and biomineralization. The uniformly distributed Mg particles slightly decreased the crystallinity of PLA. The pH value and variations in mass analysis during the in vitro degradation showed that the Mg incorporation could effectively neutralize the acidic products of PLA, as well as induce more apatite deposition. Great decrease in molecular weight of 2 wt% and 5 wt% Mg/PLA composites as compared to the neat PLA after 8 weeks' immersion made it possible to modulate the degradation rate of the PLA by controlling the proportion of Mg content and other key factors such as size and shape of the Mg reinforcements. In vitro cell culture revealed good biocompatibility of Mg/PLA, and the favorable characteristic for osteoblastic cells to adhere and spread. The cellular biomineralization results demonstrated significantly higher bone-like nodules deposition (both in number and area) achieved on the composite surfaces than that on PLA surface after 14 and 28 days culture. The promoting bone-forming ability derives from the degradation of Mg particles. The study elucidated the positive effects of Mg incorporated to PLA matrix on the degradation and osteogenesis, and provide an alternative for the currently used PLA implants.